(untitled) (Kinesiology, 2018)
Accumulation of abdominal fat during adolescence is associated with early metabolic dysfunctions and interrupting bone metabolism. This study aimed at investigating the effects of taekwondo training on abdominal fat and bone metabolism in obese adolescents. Twenty male obese adolescents, with a body mass index above 95th percentile (BMI: 29.4±1.90 kg/m2), aged 12-15 years, were assigned to the taekwondo training group (TKD, n=11) and control group (CON, n=9). Supervised taekwondo training was performed for 60 minutes/day, three times/week at 60-80% of participants’ heart rate reserve for 16 weeks. Body composition and bone mineral density (BMD) were estimated by dual X-ray absorptiometry. A computerized tomography scan was applied to estimate total abdominal fat (TAF), abdominal visceral fat (AVF), abdominal subcutaneous fat (ASF), and AVF to ASF ratio (VSR). Blood samples were analyzed for adipocytokines (leptin and adiponectin) and bone turnover markers (osteocalcin- OC and C-terminal telopeptide-CTx). There were significant interaction effects between abdominal fat variables and training where TAF (p<.01) and AVF (p<.05) decreased in TKD group. Bone metabolism including bone formation (OC, p<.05) and resorption markers (CTx, p<.05) were significantly increased only in the TKD group. The present study suggests that taekwondo training can be an effective afterschool activity program for providing health benefits including improving abdominal fat and bone metabolism in obese adolescents. Key words: abdominal fat, visceral fat, bone turnover markers, obese adolescent, taekwondo